COGNITIVE READING STRATEGIES FOR COMPREHENSION - Sevara Usmonova; O`g`iloy Hoshimova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Most people think that reading improves the knowledge and widen horizon. However, they do not know when and how reading affects in enhancing knowledge. There are many challenges among readers how to improve their reading skills, not only for non-natives, but also for natives it can be perplexing.